Parasites of cetaceans stranded on the Pacific coast of Costa Rica - De Oliveira, Jaqueline; Morales, Juan Alberto; González-Barrientos, Rocio; Hernández-Gamboa, Jorge; Hernández-Mora, G. (Veterinary Parasitology, 2011)
Information regarding parasitic fauna of cetaceans from Costa Rica is provided for the first time. A total of 25 stranded dolphins and whales were examined between 2001 and 2009, including striped dolphin (Stenella coeruleoalba) (n = 19), pantropical spotted dolphin (S. attenuata) (n = 2), spinner dolphin (S. longirostris) (n = 1), bottlenose dolphin (Tursiops truncatus) (n = 1), dwarf sperm whale (Kogia sima) (n = 1) and Cuvier’s beaked whale (Ziphius cavirostris) (n = 1). Pathological findings associated with the parasites are also presented. In the most representative dolphin species, S. coeruleoalba, the prevalence of parasites was 89.5%; moreover, all examined specimens of S. attenuata, S. longirostris, T. truncatus and Z. cavirostris presented parasites. No parasites were recovered from K. sima. Fourteen helminth taxa were identified, including six species of cestodes (Strobilocephalus triangularis, Tetrabothrius forsteri, Trigonocotyle sp., Phyllobothrium delphini, Monorygma grimaldi, Tetraphyllidea gen. sp. plerocercoid), four digeneans (Nasitrema globicephalae, Brachycladium palliatum, B. pacificum and Oschmarinella albamarina) and four nematodes (Anisakis spp., Halocercus lagenorhynchi, Halocercus sp. and Crassicauda anthonyi). A commensal crustacean, Xenobalanus globicipitis, was also identified. All identified parasites representing new geographic records for the Pacific coast of Central America and new host records are presented. Parasitological information is valuable for conservation of cetaceans in Pacific coast of Costa Rica. Se proporciona por primera vez información sobre la fauna parásita de cetáceos de Costa Rica. Un total de 25 delfines varados y ballenas fueron examinados entre 2001 y 2009, incluyendo delfines rayados (Stenella coeruleoalba) (n = 19), delfines manchados pantropicales (S. attenuata) (n = 2), delfines giradores (S. longirostris) ( n = 1), delfín mular (Tursiops truncatus) (n = 1), cachalote enano (Kogia sima) (n = 1) y ballena picuda de Cuvier (Ziphius cavirostris) (n = ...